Socio-environmental path of indigenous territories in the Venezuelan Amazon - Becerra, Melgris José (2021)
The Venezuelan Amazon is a place that has not achieved a good capillarity among geography professionals in Venezuela. This region has been characterized (in books) as an inhospitable and unfathomable region. This text intends to demonstrate that geographic knowledge is developed in different cultures and societies in which their own knowledge converges and is key to territorial governance and management of the territory. It narrates a personal life story that clarifies, questions, and amalgamates knowledge learned in the academy and local experiences with the indigenous peoples of the Venezuelan Amazon. Finally, it concludes that experiences enrich knowledge and are the basis for understanding the territories where diverse voices, nuances and daily elements that shape the local geographic space and life in the Amazon converge.